2007
DOI: 10.1097/01.olq.0000258306.20287.a7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination of Men Who Have Sex With Men Attending an Urban STD Clinic: Impact of an Ongoing Vaccination Program, 1998–2003

Abstract: Hepatitis B vaccination can be integrated into STD clinic services with reasonable levels of vaccine acceptance and series completion. The increase in vaccination coverage over time indicates that a sustained hepatitis B immunization program can achieve acceptable vaccine coverage in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…Since sexual activity is the most commonly reported risk factor among persons with acute hepatitis B, STI clinics can serve as a particularly effective venue for delivering Hepatitis B vaccinations. 29,30 The findings of the present study support the need for a more proactive approach to vaccinate uninfected adults at risk for hepatitis B.…”
Section: Stis Among South Indians At High Risk For Hiv Infection 679supporting
confidence: 57%
“…Since sexual activity is the most commonly reported risk factor among persons with acute hepatitis B, STI clinics can serve as a particularly effective venue for delivering Hepatitis B vaccinations. 29,30 The findings of the present study support the need for a more proactive approach to vaccinate uninfected adults at risk for hepatitis B.…”
Section: Stis Among South Indians At High Risk For Hiv Infection 679supporting
confidence: 57%
“…The annual number of client visits to these STD clinics ranged from 2,883 9 In addition, staff from all six STD clinics reported that clients have increasingly reported prior vaccination. By the late 1990s, all of the states represented by participating clinics had laws requiring hepatitis B vaccination for middle school or high school entry.…”
Section: Resultsmentioning
confidence: 99%
“…37 It has been shown that hepatitis B vaccination can be integrated into STD clinic services with reasonable levels of vaccine acceptance and series completion. 38 In summary, a high prevalence of HBV serologic markers suggesting previous exposure to or natural infection was found to be high among Peruvian MSM and was also found to be associated with high-risk sexual behavior, syphilis, HIV-1, and HSV-2 infection, suggesting sexual contact as a main mode of transmission. Given the potential likelihood of HBV acquisition and transmission, MSM in Peru constitute a target population for further HBV preventive interventions.…”
Section: Discussionmentioning
confidence: 99%